Implementation of Webbed Type Integrated Learning to Improve Student Learning Activities - Desi Aulia; Chairul Azmi; Yanti Fitria (Jurnal Penelitian Pendidikan IPA, 2023)
Integrated learning is a learning approach that adapts to the level of student development and gives students the opportunity to learn both individually and in groups. The study aims to provide an overview of the application of webbed-type integrated learning in primary schools. The subjects in the study are teachers in Gugus II Kecamatan Payakumbuh Timur. The research is carried out using descriptive qualitative methods, where data collected from the results of observations, interviews, and documentation is analyzed descriptively to describe the application of webbed-type integrated learning in elementary schools. Research results show that in integrated learning of the webbed type, learning starts from themes in everyday life that are close to the student environment, so learning becomes more meaningful. In the learning process, students are actively involved in various fun learning activities. Thus, it can be concluded that integrated learning using the webbed type is very suitable for application in elementary schools because it can improve student learning activities.